Increasing Knowledge and Behavior in Selecting Healthy Food and Drinks among School Children Through the Thematic Gamification Program "Monopoly on Healthy Snacks": Meningkatkan Pengetahuan dan Perilaku Pemilihan Makanan dan Minuman Sehat pada Agregat Anak Sekolah Melalui Program Gamifikasi Tematik “Monopoli Jajanan Sehat” - Ni Luh Putu Dian Yunita Sari; Triana, Komang Yogi; Prastikanala, I Kadek (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
A phenomenon in the growth aspect of the child age group is obesity. Obesity is influenced by behavior in choosing food and drinks consumed daily. The preventive efforts that have been carried out so far have focused on lecture methods and media distribution. However, an educational approach in the form of games has not been implemented. The aim of this program is to implement a monopoly game with the theme "Healthy Snacks Monopoly" to increase knowledge and behavior in choosing healthy foods and drinks. This game is played in groups, for 30 minutes, and students can buy the food and drinks provided. Monitoring is also carried out for one month through the homeroom teacher. The results obtained were that students showed an increase in aspects of knowledge and behavior in choosing healthy food and drinks. This game can be applied to teachers, parents and health workers who are responsible for the health of school children to improve healthy lifestyles, especially in choosing food and drinks.